The party and the masses : an interorganizational analysis of Lenin's model for the bolshevik revolutionary movement. - Lundquist, Lennart (Stockholm : Almqvist & Wiksell International, 1982)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Lenin, Vladimir; communisme; Sovjet-Unie.